2010
DOI: 10.1143/apex.3.081001
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low On-Resistance and High Breakdown Voltage Observed in Vertical GaN Schottky Barrier Diodes with High-Mobility Drift Layers on Low-Dislocation-Density GaN Substrates

Abstract: Vertical GaN Schottky barrier diodes (SBDs) were fabricated on freestanding GaN substrates with low dislocation density. High quality n-GaN drift-layer with an electron mobility of 930 cm2 V-1 s-1 was obtained by optimizing the growth conditions by reducing the intensity of yellow luminescence using conventional photoluminescence measurements. The specific on-resistance (RonA) and the breakdown voltage (VB) of the SBDs were 0.71 mΩ cm2 and over 1100 V, respectively. The figure of merit (VB2/RonA) was 1.7 GW/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(143 citation statements)
references
References 13 publications
3
137
1
2
Order By: Relevance
“…Recent research on diodes has indicated that the quality of GaN substrates has become high enough to apply them to high-voltage devices [28,29,30]. We have determined that edge and mixed (edge + screw) dislocations in the GaN substrate do not induce a leakage current even at a dislocation density of ∼10 6 cm −2 [31].…”
Section: Vertical Gan Power Devicesmentioning
confidence: 99%
“…Recent research on diodes has indicated that the quality of GaN substrates has become high enough to apply them to high-voltage devices [28,29,30]. We have determined that edge and mixed (edge + screw) dislocations in the GaN substrate do not induce a leakage current even at a dislocation density of ∼10 6 cm −2 [31].…”
Section: Vertical Gan Power Devicesmentioning
confidence: 99%
“…[15] and Saitoh et al [12] reported a DD of 1 × 10 6 cm −2 for MOCVD GaN Schottky diodes with a record power figure of merit of 1.7 GW cm −2 . When the HEMT surface is analyzed with SEM and atomic force microscopy (AFM), it is noticeable that the surface was composed of mounds, in the form of a truncated elliptical parabola (figure 2).…”
Section: Nanoscale Homoepitaxial Mode Of Growth and Morphologymentioning
confidence: 99%
“…The highest quality GaN epitaxial layers would ideally be achieved by homoepitaxy using a GaN substrate which is identical in crystal structure, lattice constant and thermal expansion coefficient. This homoepitaxy template can be achieved by means of a freestanding (FS-GaN) crystal, (obtained after the growth and separation of several hundred micrometers of GaN on a foreign substrate), but such FS-GaN layers still contains several types of imperfections such as scratches and/or edge pits [10][11][12][13][14][15][16][17]. The inherent FS-GaN defects extend into the HEMT active layers and may degrade the charge transport mechanisms, particularly increasing the HEMT off-state leakage currents which, in turn, reduces the breakdown voltage.…”
mentioning
confidence: 99%
“…HVPE produced GaN substrates were used to build Schottky rectifiers with threading dislocation densities < 1x 10 6 cm -2 and have exhibited n-type conductivity with resistivity value as low as .01 Ωcm. A 5 μm epitaxial layer was deposited on top of the bulk substrate using MOCVD [53] with Si concentration of 8x10 15 cm -3 . 1 μm thick PECVD deposited SiN X was used as the dielectric layer, and the field plate structure was formed by Schottky contact overlapped with dielectric as illustrated in the figure 2-8.…”
Section: Lateral Diodesmentioning
confidence: 99%
“…The goal of edge termination techniques is to achieve an electric field distribution as close to the ideal case as possible. A number of edge modification techniques have been used in the literature, such as field plates [53], damage implants [56], guard rings [33], and different combinations of these strategies [58][59][60], as shown in figure 2-11. In a field plate structure, the Schottky contact extends over the dielectric.…”
Section: Field Crowdingmentioning
confidence: 99%